What Shapes the Attitudes Towards Paying Taxes? Evidence from Switzerland, Belgium and Spain - Benno Torgler; Friedrich Schneider (Center for Research in Economics, Management and the Arts (CREMA), 2005)
There is considerable evidence that enforcement efforts cannot fully explain the high degree of tax compliance. To resolve this puzzle of tax compliance, many researchers have argued that citizens' attitudes toward paying taxes or tax morale, seen as the intrinsic motivation to pay taxes, can help to explain the high degree of tax compliance. However, most studies treat tax morale as a black box without discussing which factors shape it. Additionally, there is a lack of empirical evidence in the tax compliance literature that investigate attitudes towards paying taxes in Europe. Thus, a unique aspect in this paper is to examine citizens' attitudes towards paying taxes in the three European countries Switzerland, Belgium and Spain, allowing thus to investigate in detailed way the impact of internal and external institutions.
Keywords: H26; H73; 330; Tax Morale; Tax Compliance; Tax Evasion; Internal and External Institutions